Impact of blue-light filtering intraocular lens implantation on the quality of sleep in patients after cataract surgery. Issue 51 (December 2016) - Feng, Xue; Xu, Ke; Hao, Yansheng; Qi, Hong
Abstract: Background: There are 2 main types of intraocular lens (IOL) currently implanted in patients after cataract surgery. Till now, we do not know exactly what the effect of intraocular lens implantation will be on the quality of sleep after cataract surgery. Methods: The binocular BF-IOL (BF-IOL Groups) and UVB-IOL (UVB-IOL Groups) implantations were performed in 60 and 59 cataract patients, respectively. Pittsburgh Sleep Quality Index (PSQI) questionnaires were administered to evaluate the quality of sleep in patients preoperatively, 1 month (1 m) and 12 months (12 m) postoperatively. Independent sample test and χ 2 test were used to evaluate the difference between the 2 groups; one-way ANOVA was used to evaluate the difference preoperatively and postoperatively in each group. The rank sum test was used for statistical analysis of 7 independent sleep components in PSQI. Results: As compared to preoperatively, the PSQI overall scores in both groups improved significantly postoperatively ( P = 0.00 at 1 m and 12 m). Among the 7 components of PSQI, 2 of them (sleep latency and daytime dysfunction) improved greatly postoperatively in both groups ( P < 0.05). Although the improvement of PSQI overall score in the UVB-IOL group was greater than that in the BF-IOL Group only at early time (1 m) postoperatively ( P = 0.00), but not late time (12 m, P > 0.05) after the cataract surgery. Conclusion: The sleep quality of cataract patients improved after IOL implantation, regardless of the type of IOL, suggesting that BF-IOL might serve as an alternative to conventional UVB-IOL without a detrimental effect on quality of sleep after cataract surgery.